Prospective study of prognostic value of Raf kinase inhibitory protein and pretreatment plasma Epstein–Barr virus DNA for distant metastasis in locoregionally advanced nasopharyngeal carcinoma. Issue 4 (18th May 2012) - Li, Si‐Wei; Wang, Hua; Xiang, Yan‐Qun; Zhang, Hai‐bo; Lv, Xing; Xia, Wei‐Xiong; Zeng, Mu‐Sheng; Mai, Hai‐Qiang; Hong, Ming‐Huang; Guo, Xiang
Abstract Background The purpose of this prospective study was to investigate the predictive significance of Raf kinase inhibitory protein (RKIP) in locoregionally advanced nasopharyngeal carcinoma (NPC) and its effect on distant metastasis. Methods The usual immunohistochemical stainings were performed to detect RKIP expression of cancer tissues from 210 patients with advanced NPC. After DNA samples from pretreatment plasma from these patients were extracted, real‐time polymerase chain reaction (PCR) was performed to quantitatively analyze plasma Epstein–Barr virus (EBV) DNA. Results RKIP expression was significantly different for different N classifications and WHO pathologic grades, respectively (p < .05). Cox regression confirmed RKIP and EBV DNA were independent prognostic markers for 5‐year distant metastasis‐free survival (DMFS). In the high RKIP expression group, chemotherapy had a positive effect on improved DMFS, but not in the low RKIP expression group. Conclusions RKIP could be identified as an independent prognostic factor on DMFS. For each combined treatment modality, the different impact of chemotherapy on distant metastasis might be related to the RKIP expression level. © 2012 Wiley Periodicals, Inc. Head Neck, 2013